Explaining the model of value creation of tax income and gross domestic product based on tax system reforms - Bahram Ramazani; Mojtaba Malekichoobari; Sina Kheradyar (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of the current research is to explain the pattern of value creation from tax revenue and gross domestic product based on tax system reforms. According to its purpose, the research method is applicable; in terms of execution method, it is mixed (qualitative-quantitative), and in terms of nature and method, it is exploratory-explanatory. The statistical population of the research in the qualitative part includes 12 managers and assistants of the tax system, experts and consultants selected by non-probability sampling method with multiple strategies (intensity and snowball); and in the quantitative part it includes 265 people from those who were working in the administration of tax affairs of Tehran province, selected by random cluster sampling method. Data collection was done by semi-structured interviews in the qualitative part; and by the questionnaire in the quantitative part. Qualitative data analysis was done using the data-based method with MAXQDA software; and the quantitative part with Smart PLS. The findings of the research showed that the formation of the concept of tax revenue and gross domestic product value creation indicators based on tax system reforms includes 69 components in the form of 43 categories and 17 major categories. The conceptual model of the research has been implemented during the investigated relationships. The results of the research show that the influence between the components in the quantitative study had a necessary and appropriate level. Conclusion of the Tax system reforms focusing on value creation of tax revenue and GDP are very important in the economic and social development of countries. It is possible to create added value, sustainable development, reduce poverty and improve social skills by improving the tax system and related reforms. Extended Abstract Introduction The tax system, as one of the main tools of the government to collect public revenues and provide financial resources, plays a significant role in determining income distribution and affecting social welfare. This system can have a significant impact on GDP (production and economic growth) and therefore, its proper design and modification can help improve economic and social indicators (Haj Mahmoud Attar & Araei, 2022). Previous studies in the field of tax system reforms and their impact on GDP have been considered as one of the most popular topics in economic sciences. Research shows that the tax system and tax requirements can have a significant impact on GDP, and improving tax revenue can contribute to economic growth. (Akcigit et al, 2018). The economic infrastructure of any organization is formed by the financial issues of that organization, the establishment of a prosperous economic system with a strong financial infrastructure in the country helps to increase income and strengthen the financial health of the budget by establishing the optimal and appropriate relationship between limited resources and unlimited human needs. Human resources are certainly one of the most important pillars of organizations and each and every employee is involved in the process of development and progress of organizations, so one of the reasons for the success of organizations is to have taxpayers who strive beyond their duties. The inefficiency of the tax system has led to the emergence of challenges whose long-years persistence has led to problems. The low ratio of taxes to GDP in recent decades has caused taxes to play a small role in the country's economy despite all the measures and efforts, so in this research we are looking for an answer to the question: What is the pattern of value creation from tax revenue and gross domestic product based on tax system reforms? Theoretical Framework Value creation of tax revenue and gross domestic product Reforming the system of exemptions and tax facilities for important industries and less developed areas will create balance and uniform development throughout the country. Also, with the improvement of the tax transfer system and the progressive reduction of heavy tax effects, the incentives for tax fraud will decrease and public trust in the tax system will increase. This balance and positive relationship between the tax system and GDP leads to sustainable economic growth, reducing poverty, and improving social skills (Drummond et al, 2023). Increasing tax transparency and information Increasing tax transparency and information means providing accurate, comprehensive, and accessible information about taxes and the tax process. This action helps to strengthen tax justice, reduce tax evasion, and better structure of the tax system. Tax information related to any person or entity should be made available to the public. This information includes income, tax paid, exemptions, and other tax details. Transparency and knowing the tax reality of each individual is guaranteed by providing access to this information, and illegal activities such as tax evasion can be prevented (Panahian et al, 2012). Ramezani et al, (2024) investigated the explanation of the improvement pattern of tax revenue and GDP based on the behavioral reforms of the tax system. The findings of the research showed that the improvement of tax revenue and gross domestic product based on the behavioral reforms of the tax system (including the themes of causal conditions: economic, social, and political; central conditions: tax structure, reducing tax corruption, reforming the tax monitoring and enforcement system; conditions Strategies: promoting tax culture, decreasing tax discrimination, and tax system reform; intervening conditions: legal reforms and tax policies; background conditions: level of economic development, level of tax ability, and establishment of a fair tax system; conditions of consequences: increase in production, increase in economic competitiveness, and reduction of tax corruption) can have an effect. Jiang et al, (2023), in a research titled government social media and corporate tax avoidance showed that the higher the performance quality of government social media tax offices, the lower the degree of tax avoidance of local firms, which works by reducing tax avoidance incentives and increasing the difficulty of committing tax avoidance. In addition, government social media have a substitution effect on tax enforcement and administration. They also found that government social media should focus on strengthening their official and professional characteristics. Due to recent significant changes in the way companies handle taxes, the proportion of information that tax offices send in system operations should be increased accordingly. Research methodology The research method is applicable in terms of purpose; mixed (qualitative-quantitative)in terms of execution method, and exploratory-explanatory in terms of nature and method. The statistical population of the research in the qualitative part includes 12 managers and assistants of the tax system, experts and consultants selected by non-probability sampling method with multiple strategies (intensity and snowball); and in the quantitative part it includes 265 people from those who were working in the administration of tax affairs of Tehran province, selected by random cluster sampling method. Data collection was done by semi-structured interviews in the qualitative part; and by the questionnaire in the quantitative part. Research findings Qualitative data analysis was done using the data-based method with MAXQDA software; and the quantitative part with Smart PLS. The findings of the research showed that the formation of the concept of tax revenue and gross domestic product value creation indicators based on tax system reforms includes 69 components in the form of 43 categories and 17 major categories. The conceptual model of the research has been implemented during the investigated relationships. The results of the research show that the influence between the components in the quantitative study had a necessary and appropriate level. Conclusion of the Tax system reforms focusing on value creation of tax revenue and GDP are very important in the economic and social development of countries. It is possible to create added value, sustainable development, reduce poverty and improve social skills by improving the tax system and related reforms. Conclusion The current research was conducted with the aim of explaining the model of value creation from tax revenue and gross domestic product based on tax system reforms. The results of this research are in agreement with the results of Ramezani et al, (2024), Jiang et al, (2023), Cateia & Fereira (2023), Hayo & Mierzwa (2022), Yu (2022), Fstmawati (2022), Sarmad et al, (2022), Nguyen et al, (2021), Mohajeri et al, (2020), Hasanvand et al, (2020), and Makiyan et al, (2019). Hayo & Mierzwa (2022) analyzed the dynamic results of local forecasts by using shocks of interest, narrative information about future tax changes in the quarter of their introduction to the legislative body. After the tax cut is enacted, economic activity in the United States (UK) decreases (increases), but remains unaffected in Germany. When they allowed responses to vary over the business cycle, they found evidence that US GDP fell regardless of the business cycle, while UK GDP only rose in non-recessionary times. German GDP increases (decreases) during a recession (non-recession). According to the results of the research, the following suggestions were presented: